Konstruktivisme dalam Pendidikan Abad 21 Membangun Siswa yang Kreatif Inovatif dan Berpikir Kritis dalam Pembelajaran Pendidikan Jasmani, Kesehatan dan Olahraga di SMPN 3 Cibatu Purwakarta - Ahmad Hamdani; Dewi Ratnaningsih; Reza Nuril Fahmi; Neneng Yusmawati Muniroh; Ricky Yoseptry (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2025)
Physical education, health, and sports is one of the most important subjects in enhancing students’ physical, mental, and social abilities. The learning approach applied in this study is constructivist learning theory, which emphasizes the construction of knowledge by students through experience and reflection. Education should not merely focus on the transmission of knowledge from teachers to students, but should also develop students’ abilities to think critically, solve problems, and innovate. This study employs a qualitative research design with a constructivist approach. It aims to develop creative and innovative students through physical education, health, and sports learning at SMP Negeri 3 Cibatu, Purwakarta. The research design uses a classroom action research model. The results show that the critical thinking ability of students in the experimental group was 82.3, while that of the control group was 71.5. This indicates that students who participated in physical education, health, and sports learning using constructivist theory demonstrated better critical thinking skills than students who did not participate in constructivist-based physical education, health, and sports learning.